The Ritter Reaction of 2‐Oxoaldehydes at Room Temperature: Divergent Behaviour towards Acid Strength. Issue 34 (7th December 2017) - Khan, Shahnawaz; Kumar, Atul; Gupta, Raman; Ahmed, Qazi N.
Abstract: An efficient, novel, atom economical and selective amidation method for the generation of mono and di‐Ritter products using 2‐oxoaldehydes under acidic environment at room temperature was successfully developed. The di‐Ritter products obtained are accessed in good yields when stirred in the presence of 20 mol % H2 SO4, and the mono products were selectively obtained in moderate yields with CuOTf as catalyst. However, the yields of the latter were optimized by the addition of SeO2 . Abstract : An efficient, novel, atom economical and selective amidation method for the generation of mono and di‐Ritter products using 2‐oxoaldehydes under acidic environment at room temperature was successfully developed. The di‐Ritter products obtained are accessed in good yields when stirred in the presence of 20 mol % H2 SO4, and the mono products were selectively obtained in moderate yields with CuOTf as catalyst. However, the yields of the latter were optimized by the addition of SeO2 .